The Vital Roles of LINC00662 in Human Cancers - He, Yuting; Xu, Yating; Yu, Xiao; Sun, Zongzong; Guo, Wenzhi (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) play crucial roles in many human diseases, particularly in tumorigenicity and progression. Although lncRNA research studies are increasing rapidly, our understanding of lncRNA mechanisms is still incomplete. The long intergenic non-protein coding RNA 662 (LINC00662) is a novel lncRNA, and accumulating evidence suggests that it is related to a variety of tumors in multiple systems, including the respiratory, reproductive, nervous, and digestive systems. LINC00662 has been shown to be upregulated in malignant tumors and has been confirmed to promote the development of malignant tumors. LINC00662 has also been reported to facilitate a variety of cellular events, such as tumor-cell proliferation, invasion, and migration, and its expression has been correlated to clinicopathological characteristics in patients with tumors. In terms of mechanisms, LINC00662 regulates gene expression by interacting with both proteins and with RNAs, so it may be a potential biomarker for cancer diagnosis, prognosis, and treatment. This article reviews the expression patterns, biological functions, and underlying molecular mechanisms of LINC00662 in tumors.